1987
DOI: 10.1111/j.1432-1033.1987.tb13375.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylene treatment on the concentration of fructose‐2,6‐bisphosphate and on the activity of phosphofructokinase 2/fructose‐2,6‐bisphosphatase in banana

Abstract: Preclimacteric bananas fruits were treated for 12 h with ethylene to induce the climacteric rise in respiration. One day after the end of the hormonal treatment, the two activities of the bifunctional enzyme, phosphofructokinase 2/fructose-2,6-bisphosphatase started to increase to reach fourfold their initial value 6 days later. By contrast, the activities of the pyrophosphate-dependent and of the ATP-dependent 6-phosphofructo-1 -kinases remained constant during the whole experimental period, the first one bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
4
25
1
Order By: Relevance
“…During ripening our bananas behaved in the same way as those studied by Mertens et al [2]. The latter reported that C 0 2 production rose from 20 to 80 p1 .…”
Section: Relationship Between Fru(26)pz and Respiration During Ripeningsupporting
confidence: 69%
See 4 more Smart Citations
“…During ripening our bananas behaved in the same way as those studied by Mertens et al [2]. The latter reported that C 0 2 production rose from 20 to 80 p1 .…”
Section: Relationship Between Fru(26)pz and Respiration During Ripeningsupporting
confidence: 69%
“…Thus although the amount of Fru(2,6)Pz that we detected in the extracts rose markedly during ripening this rise was very closely paralleled by a corresponding increase in recovery. This was demonstrated specifically for the methods described by Mertens et al [2] and by Beaudry et al [3]. The recoveries that we found for samples extracted in Hepes were, however, measurable and sufficiently consistent for us to be able to use them to correct the observed values for Fru(2,6)Pz to give a truer estimate of the actual amount present in vivo.…”
Section: Relationship Between Fru(26)pz and Respiration During Ripeningmentioning
confidence: 85%
See 3 more Smart Citations